Caenorhabditis elegans: um modelo experimental para a análise dos efeitos agudos de extratos de erva-mate (Ilex paraguariensis) e uma ferramenta para a potencialização do Ensino de Ciências na Escola Básica - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Ilex paraguariensis (St. Hilaire) popularly called yerba mate, it is a tree species that grows naturally in the forests of South America and is widely used in the preparation of a peculiar drink known as mate, or tererê, depending on where is consumed. Among the known substances of the mate are polyphenols, saponins, xanthines, vitamins and minerals and there is an interest in elucidating the effects of these components. Due to this, the present study evaluated the effects of acute exposure to extracts of different herbs mate (I. paraguariensis), from Argentina, Brazil and Uruguay in C. elegans. In order to obtain extracts with similar composition to ingested by the population, prepared to drink the traditional way and we used a form of extraction that mimics its consumption. From these extracts (mates) tests were performed for survival, locomotion, reproduction, longevity, stress resistance and level of reactive species using the Bristol N2 strain of C. elegans. We also found activation of the transcription factor DAF-16 and the regulation of the enzymes SOD and Catalase-3 using strains that have transgenic green fluorescent protein (GFP) fused to these pathways, the nematode C. elegans. It was possible that the extracts did not cause lethality and were able to significantly increase the II lifespan of this model organism. We point out the possibility that this result is mediated by activation of the transcription factor DAF-16, a gene homologous to the FOXO (humans), responsible for regulating various biological processes such as longevity, reproduction and stress response. This factor, when activated translocates from the cytosol to the nucleus and activates the expression of target genes encode enzymes that antioxidants, such as SOD-3. Although the extracts which have significantly increased the longevity also increased translocation of-16 to DAF core, interestingly not increased expression of SOD and Catalase-3, indicating that other pathways may be involved in this effect. The Caenorhabitis elegans is a free-living nematode soil that has long been used in the context of current scientific research and besides being a great and well-described model can be used to enhance the Teaching of Science in Primary School through an innovative. So in addition to scientific research, this paper proposed a differentiated work for Teaching Science and Health in the early years of the Basic School, using C. elegans as alternative model. This study summarizes an important contribution to future research, both because the first time shows the effects of extracts obtained from different nationalities in the way people usually consume in C. elegans, and the starting point for the investigation of mechanisms involved in the effects described above, as it has shown that alternative methods of scientific experimentation can enhance learning science and to improve understanding of the students, through the awakening of curiosity and stimulate greater effective participation in classes, indicating that innovative methods should be further explored.
Caenorhabditis elegans: an experimental model for the analysis of the acute effects of extracts of yerba mate (Ilex paraguariensis) and a tool for empowerment of Science Teaching in Primary School
Keywords: DAF-16; Antioxidante; Longevidade; Ensino fundamental; Antioxidants; DAF-16; Longevity; Basic school; Teaching